The Royal Mortuary Cult at Nuri, 593–431 BC - Doll, Susan K..
The identification of the texts on the Nuri funerary stelae from the pyramid chapels of Anlamani, Aspelta, Amaniastabarqo, Siaspiqo, and Talakhamani (probably also Malowiebamani) as extracts from the Ritual of the Royal Ancestors has been made several times in the Egyptological literature, but only casually and in passing. This paper presents a translation and overview of the texts and discusses several aspects of their use in the Napatan context. In addition to segments of the Ritual of the Royal Ancestors, some additional phrases and spells were taken from other sources. These extracts were carefully selected and organized, and doubtless reflect the actual order of events in the liturgy honoring the dead kings at Nuri. The ritual events included initial purification of the offerings, water, wine, and milk libations, censing, a ?tp d? nsw, and a summoning of the king’s spirit to the chapel from the tomb chamber below in order to partake of the offerings. A priest taking the part of Thoth was apparently the performer of the ritual. During the approximately 175 years of the employment of the Ritual of the Royal Ancestors at Nuri, it was added to and developed by each king who used it, reflecting the fact that these ceremonies were not static and purely imitative of earlier examples, but were a living and vibrant part of the Nuri mortuary cult.